Effects of peach branch organic fertilizer on the soil microbial community in peach orachards - Liu, Chenyu; Han, Defeng; Yang, Haiqing; Liu, Zhiling; Gao, Chengda; Liu, Yueping (Frontiers in Microbiology, 2023)
Peach branches is a by-product of peach industry. Making peach branch waste into peach branch organic fertilizer (PBOF) is a promising strategy of ecological utilization. In this study, the effects of PBOF on the yield and quality of peach fruit, chemical properties of bulk soil, and soil bacterial communities were investigated in a peach orchard. The results showed that the yield and sugar/acid ratio of two high-level PBOF treatments (SDH.4 and SKR.4) was higher than no fertilization treatment (CK), but there was no significant difference compared to the commercial organic fertilizer treatment (SYT.4). Moreover, the three fertilizer treatments increased soil nutrients such as soil organic matter (SOM) and available potassium (AK), compared to CK. Furthermore, PBOF increased the relative abundance of beneficial bacteria, and enhanced the soil bacterial co-occurrence pattern and the potential function of bacterial communities to degrade exogenous compounds. In addition, thanks to the local policy of encouraging the use of PBOF, the use cost of PBOF is lower than commercial organic fertilizer, which is conducive to the development of ecological agriculture.